I Heard That … : Do rumors affect hiring decisions?. (September 2015) - Dalal, Dev K.; Diab, Dalia L.; Tindale, R. Scott
<x xml:space="preserve">Abstract</x> Misinformation can have a negative impact on decision making. Little empirical attention has, however, been given to the effect of rumors, a type of misinformation, on person judgments. Although rumors have been shown to affect other areas of organizational functioning (e.g., corporate reputation, employee morale), there is a lack of research investigating how rumors may influence hiring decisions. This study argues why rumors may influence hiring decisions by drawing from attribution, social judgment, and judgment and decision making theories, and provides an experimental investigation of this argument. Although participants reported not believing and being less likely to use the rumor, rumors were not discounted when determining if an individual should be hired. In short, results suggest that rumors impacted hiring decisions.